Fekunditas, Diameter Telur, Persentase Fertilitas, Dan Daya Tetas Pada Strain Ikan Cupang (Betta Splendens) Yang Berbeda - Darmawan Setia Budi, S.Pi., M.Si; Dian Pebianti; Akhmad Taufiq Mukti; Laksmi Sulmartiwi; Lailatul Lutfiyah; Mohammad Faizal Ulkhaq (Airlangga University, 2023)
Betta fish (Betta splendens) has export and import potential. Several popular betta fish strains include halfmoon, crown tail, double tail, and placard. We used the observation method to observe four betta fish strains with five replications. The four fish strains were spawned and will be dissected to obtain the female betta fish's gonads. The parameters observed in this study were fecundity, egg diameter, fertility, and hatchability. This study's data analysis method was analysis of variance (ANOVA) with Duncan's multiple range test. Based on the findings of the observations, it is known that the results of betta fish spawning and gonadal dissection on these various betta fish strains show a significant difference in fish fecundity (P 0.05). However, no significant difference in egg diameter, fertility, or hatchability was observed (P > 0.05). Betta splendes strains differ in terms of fecundity, fertility, hatching rate, and egg size.